Exploring the Role and Regulation of HIF-1 in Manganese Toxicity Using Caenorhabditis elegans as a Model - Zehua Tao (Proceedings)
Introduction: Chronic manganese exposure has been associated with multiple health consequences, including neurological, behavioral, and cognitive impairments [...]